Woman-focused development programme improves child survival in rural Bangladesh - Bhuiya, Abbas; Chowdhury, Mushtaque (BRAC Research and Evaluation Division (RED), 2019)
This paper reports results from a prospective study of impact of a woman-focused development programme on child survival in Matlab, a rural area of Bangladesh. A total of 5,567 children born during 1993-96 in the study area were followed till the end of December 1996. Life table analysis was carried out to compare the survival curves of children of mothers who participated in the development programme with those of comparable and richer non-participants. Hazard analysis was performed to calculate the relative risk of death controlling the effects of other independent variables. The analysis revealed a positive impact of the development programmes on survival of children.